The Cultural Art Aesthetic Behavior of Entrepreneurship Education for College Students in the Characteristics of Film and Television Media - Sun, Wei; Wang, Hongkai; Wang, Li; Ye, Lele; Chen, Peiyao (Frontiers in Psychology, 2022)
This exploration aims to promote the organic integration of innovation and entrepreneurship education and art education, further promote the reform of college Students’ cultural and aesthetic education, improve college Students’ aesthetic perception ability, and help contemporary colleges establish a correct political morality. This thesis aims to further promote the reform of college Students’ cultural and aesthetic education, improve college Students’ aesthetic perception ability, and help contemporary colleges establish correct political and moral values. First, the connotation of college Students’ aesthetic education and the definition of cultural aesthetics are introduced, which is based on the characteristics of two-way interaction, multiple selectivity, timeliness and popularization of film and television media in the new media era; then, the way of questionnaire is adopted. With five universities as the research object, 250 questionnaires are distributed, and 235 valid questionnaires are collected, with a valid response rate of 94%. Finally, through the six questions, it is concluded that 68.9% of the students watch 3–5 h a day, and 4.3% of the students watch more than 7 h; 89.4% of the students hold that the same products as stars in film and television will exert an impact on consumption. Film and television culture and art have a positive and negative impact on college Students’ cultural aesthetic perception. The positive impact is that the film and television media not only provides a good way to cultivate the aesthetic perception ability of contemporary college students, but also helps them to establish the correct aesthetic values. The negative impact is mainly reflected in two levels, namely, the vulgarization of film and television media works and the consumption of aesthetic concepts. The advantage of this exploration is to put forward the reform measures of college Students’ cultural and artistic aesthetic education under the current educational background in China to help colleges better carry out college Students’ cultural and artistic aesthetic education. Based on this, the reform measures of college Students’ cultural aesthetic education under the current education in China were put forward, so as to help colleges and universities better carry out college Students’ cultural aesthetic education.